Dysthanasia - Greš, Alen; Staver, Dijana; Ljubomir, (Scripta Medica, 2025)
Dysthanasia in medicine is the artificial prolongation and delay of death in a terminal patient, using all available means. With the advancement of sophisticated medical technologies and care, the patient can be kept alive as long as possible in the terminal stages of the disease. Such a procedure brings little benefit to the patient, while increasing suffering and sorrow for the patient and their families. The ethical implications of using medical technology in dysthanasia are complex. The challenge lies in the ethical and judicious use of modern technologies to respect the dignity and wishes of patients while avoiding unnecessary suffering.